From Motivation to Performance: The Crucial Role of Job Satisfaction in the World of Teaching Vocational Teachers - Akmal, Akmal; Fakhruddin, Fakhruddin; Budi, Cahyo (Universitas Negeri Semarang, 2026)
The performance of vocational high school (SMK) teachers is key to enhancing the relevance of vocational education to industry needs. However, evidence shows that high work motivation does not always directly correlate with performance achievements, necessitating a deep understanding of the underlying mechanisms. This study aims to analyze the role of job satisfaction as a mediating variable in the relationship between work motivation, organizational culture, and self-efficacy on the performance of SMK teachers. A quantitative method with a survey design was applied to 164 public SMK teachers in East Semarang District, using a proportional random sampling technique. Data were analyzed using path analysis and the Sobel test. The results reveal that: (1) work motivation does not have a direct effect on teacher performance; (2) job satisfaction acts as a full mediator between work motivation and performance; (3) organizational culture and self-efficacy have both direct and indirect effects through job satisfaction; (4) self-efficacy is the strongest predictor of teacher performance. The study concludes that job satisfaction functions as a psychological bridge that transforms motivation into actual performance. The scientific contribution of this research lies in demonstrating a full mediation model that revises the conventional understanding of the direct motivation-performance relationship, while also offering an integrative perspective on the development of vocational teacher performance through a simultaneous organizational-individual-psychological approach.